2020
DOI: 10.1093/cercor/bhaa356
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities of Cortical Sources of Resting State Alpha Electroencephalographic Rhythms are Related to Education Attainment in Cognitively Unimpaired Seniors and Patients with Alzheimer’s Disease and Amnesic Mild Cognitive Impairment

Abstract: In normal old (Nold) and Alzheimer’s disease (AD) persons, a high cognitive reserve (CR) makes them more resistant and resilient to brain neuropathology and neurodegeneration. Here, we tested whether these effects may affect neurophysiological oscillatory mechanisms generating dominant resting state electroencephalographic (rsEEG) alpha rhythms in Nold and patients with mild cognitive impairment (MCI) due to AD (ADMCI). Data in 60 Nold and 70 ADMCI participants, stratified in higher (Edu+) and lower (Edu–) edu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 77 publications
0
25
0
Order By: Relevance
“…However, we have also shown that the relationship between cognitive reserve and spectral features is independent from memory and executive control performance, which was taken into account through the multivariate nature of our analyses and replication of results in the cognitively normal group. Yet, the spectral signature of cognitive reserve might change as a function of the pathological substrate underlying cognitive decline ( Babiloni et al, 2021 ). Considering the small size of the CI group, it was not possible to perform reliable correlation analyses within this group.…”
Section: Discussionmentioning
confidence: 99%
“…However, we have also shown that the relationship between cognitive reserve and spectral features is independent from memory and executive control performance, which was taken into account through the multivariate nature of our analyses and replication of results in the cognitively normal group. Yet, the spectral signature of cognitive reserve might change as a function of the pathological substrate underlying cognitive decline ( Babiloni et al, 2021 ). Considering the small size of the CI group, it was not possible to perform reliable correlation analyses within this group.…”
Section: Discussionmentioning
confidence: 99%
“…In an ITALIAN‐TURKEY rsEEG study (Class A), compared to CU persons ( n = 60), ADMCI patients with high ( n = 35) and low ( n = 35) education attainments presented greater alpha source activations topographically widespread 53 . On the contrary, in relation to the ADMCI subgroup with low education attainment, the ADMCI subgroup with high education attainment displayed lower alpha source activations topographically widespread (notably, the two ADMCI subgroups had matched cerebrospinal AD diagnostic biomarkers, apolipoprotein E [ APOE ] ε4 genotyping, brain gray–white matter measures, and neuropsychological scores).…”
Section: Rseeg Measures For Ad Patients’ Stratificationmentioning
confidence: 98%
“…In quiet wakefulness, scalp rsEEG rhythms at posterior channels are dominated by alpha-band oscillations. These oscillations reflect the fluctuating cortical inhibition and the underlying widespread synchronization of cortical pyramidal neurons [186]. Indeed, studies have shown that neural signals synchronized at around 10 Hz subserve vigilance and attention [45,70,187,188].…”
Section: Discussionmentioning
confidence: 99%